2020
DOI: 10.3390/ijms21155453
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Expression Changes and Promoter Methylation of PLA2R1 in Tissues of Breast Cancer Patients

Abstract: Phospholipase A2 receptor 1 (PLA2R1) expression and its role in the initiation and progression of breast cancer are an unresolved issue. PLA2R1 was found to endorse several tumor suppressive responses, including cellular senescence and apoptosis. Previous in vitro studies demonstrated that DNA hypermethylation was highly associated with the epigenetic silencing of PLA2R1 in breast cancer cell lines. Our objective was to study the level of PLA2R1 mRNA expression and the methylation of its promoter in different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“… 57 In breast cancer, negative regulation of this gene was reported in all molecular subtypes, and promoter hypermethylation of this gene has been associated with aggressive subtypes. 58 Regarding its role in chemotherapy, PLA2R1 regulates JAK/STAT signaling, and the targeting of PLA2R1 overcomes senescence. 59 All these reports indicate that this gene could play an important role in the resistance and OS.…”
Section: Discussionmentioning
confidence: 99%
“… 57 In breast cancer, negative regulation of this gene was reported in all molecular subtypes, and promoter hypermethylation of this gene has been associated with aggressive subtypes. 58 Regarding its role in chemotherapy, PLA2R1 regulates JAK/STAT signaling, and the targeting of PLA2R1 overcomes senescence. 59 All these reports indicate that this gene could play an important role in the resistance and OS.…”
Section: Discussionmentioning
confidence: 99%
“…The knockdown of this gene in prostate cancer cells increases cell proliferation but does not affect their sensitivity to docetaxel 47 . In breast cancer, negative regulation of this gene was reported in all molecular subtypes and promoter hypermethylation of this gene has been associated with aggressive subtypes 48 . Regarding its role in chemotherapy, PLA2R1 regulates JAK/STAT signaling and the targeting of PLA2R1 overcomes senescence 49 .…”
Section: Discussionmentioning
confidence: 99%
“…Functional experiments have demonstrated that PLA2R1 controls cancer cell death by influencing mitochondrial biology. Previous studies have also demonstrated that the downregulation of PLA2R1 is related to thyroid, breast, and kidney cancers (37,38). Mitochondrial amidoxime reducing component 1 (MTARC1) is a nitric oxide synthase attached to the mitochondrial membrane that is associated with increased antioxidant capacity, which can be considered the response to counteract augmented oxidative stress (39).…”
Section: Discussionmentioning
confidence: 99%